Lipid levels in the Jiarong Tibetan’s diet at high altitudes: a cross-sectional survey - Xiaoyue, Tang; Qichuan, Qiao; Jing, Guo; Pengcuo, Sanlang; Yu, Huang; Tingxin, Li (Frontiers in Nutrition, 2023)
Despite the ongoing debate on the inconsistent and controversial effects of Tibetan diet on blood lipid levels at high altitude, this cross-sectional study was conducted to analyze the relationship between dietary practices and blood lipid levels among Jiarong Tibetan population. A total of 476 Jiarong Tibetan residents were included, in which basic demographic data, physical activity records, simplified food frequency questionnaire, and biochemical data were collected. Using multivariate logistic regression analysis, the potential associations between the variables were examined, and it was found that fat energy supply ratio increased with the elevation of altitude, while the lipid level showed an inverted U-shaped variation. However, the findings suggested that a diet rich in unsaturated fatty acids might balance the effects of the Tibetan diet on the risk of lipid metabolism disorders. Therefore, it is crucial to concentrate on the fat composition rather than the amount of fat E% intake on the plateau. The results highlighted the importance of investigating the interaction between environment and genes in lipid levels among plateau Tibetan population. However, further large-scale prospective studies are required for better understanding of the complexities involved in dietary practices and their influences on blood lipid levels.